Benign metastasizing leiomyoma: a clinical case report - Cardoso, Ana Rita (2005)
The authors present the case of a 44-year-old woman complaining of shortness of breath, with a previous medical history of hysterectomy 10 years prior to admission, admitted with multiple pulmonary nodules diagnosed on chest radiography. The histopathologic exam of the pulmonary lesions diagnosed a benign metastasizing leiomyoma. In this article we review this rare entity whose origin is still controversial but should be considered in the differential diagnosis of a woman presenting with lung nodules.